How to tell a story : the essential guide to memorable storytelling from The Moth - Bowles, Meg, 1957-; Burns, Catherine, 1969-; Hixson, Jenifer; Jenness, Sarah Austin; Tellers, Kate (Crown, 2022)
"Over the past twenty-five years, the directors of The Moth have worked with people from all walks of life-including astronauts, rock stars, Nobel Prize-winners, high school students, dental hygienists, and a retired pickpocket-to develop true personal stories that have moved and delighted millions of listeners on the Moth's Peabody Award-winning radio hour and podcast. A leader in the modern storytelling movement, The Moth also inspires thousands of people around the globe to share their stories each year. Now, with How to Tell a Story, you will learn how to uncover and craft your own unique stories, like Moth storytellers such as Mike Birbiglia, Rosanne Cash, Darryl "DMC" McDaniels, Neil Gaiman, Elizabeth Gilbert, Malcolm Gladwell, Adam Gopnik, Amanda Gorman, Padma Lakshmi, Hasan Minhaj, Tig Notaro, Boots Riley, Molly Ringwald, Krista Tippett, John Turturro, and more. Whether your goal is to make it to The Moth stage, deliver the perfect wedding toast, wow clients at a business dinner, give a moving eulogy, ace a job interview, be a hit at parties, or simply connect more deeply to those around you, stories are essential... The Moth team will help you present your most authentic self to the world-and tell stories that will forge lasting connections with coworkers, clients, friends, and family"--